Synthesis, chemical kinetics, thermodynamic and structural properties of phenyl-containing beta-diketonato complexes of rhodium (I) - Stuurman, Nomampondomise Flaurette (University of the Free State, 2007)
Rhodium compounds are one of the most widely used industrial homogeneous catalysts for organic raw material processing. Classic examples of efficacious catalyst systems are: methanol carbonylation to give acetic acid in the presence of [Rh(C0)₂I₂] complex (Monsanto prosess),¹ alkene hydroformylation on RhHCO(PPh₃)₂ catalyst, hydrogenation of olefins and acetylenes with the help of RhCl(PPh₃)₃ (Wilkinson's catalyst)² and the use of [Rh(acac)(CO)i]₂ in the hydroformylation of olefins³ (Figure 1.1). In the field of olefin polymerization, metal complexes with a coordinatively unsaturated Lewis acid metal centre are generally required, whereas for transformations such as the carbonylation of methanol, electron-rich metal centres are necessary to favour oxidative addition of Mel to Rh(I).⁴ ⁵ The high catalytic reactivity of these rhodium complexes is in many respects due to the nature of ligand surroundings.⁶ Supported rhodium carbonyl complexes form an important class of catalysts and precursors for the preparation of different supported rhodium species.⁷ The reactivity of rhodium(I) dicarbonyl complexes, and in particular, the rate of carbonyl ligand substitution, is defined by the electron state of the rhodium centre.⁶ The latter ultimately depends on donor-acceptor characteristics of chelated ligand atoms coordinated directly with the metallic centre.⁶ Kinetic and thermodynamic studies on the octahedral rhodium(III) complexes has gained momentum. This field has also given rise to the important discovery of the photosensitivity of rhodium complexes. β-diketone complexes of Rh(I) of the type [Rh(β-diketone)(D)₂ (where D are electron donors such as CO, ethylene and dienes) undergo substitution reactions with a large variety of ligands. To examine these reactions, knowledge of the relative 𝘵𝘳𝘢𝘯𝘴-effect of these ligands is necessary. The unexpected discovery of the antitumor activity of cisplatin has opened up the 'era of inorganic cytostatics' .⁹ In the search for new organometallic compounds or inorganic coordination complexes with antitumor properties, it was found that some rhodium(!) complexes, for example [Rh(acac)(cod)] (acetylacetonate- I ,5-cyclooctadienerhodium(I)), showed antineoplastic activity comparable to, or even better than that of 𝘤𝘪𝘴𝘱𝘭𝘢𝘵𝘪𝘯. ¹º ¹¹
Dissertation (M.Sc.(Chemistry))--University of the Free State, 2007
Keywords: β-diketone; Rhodium(I); Oxidative addition; pKₐ'; Group electronegativity; Crystallography; Rhodium compounds -- Synthesis